2013
DOI: 10.1039/c3ra43306d
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of sodium glycyrrhetinate into a hydrogel: characterisation and properties

Abstract: Sodium glycyrrhetinate, a simple triterpenoid derivative, was found to form a hydrogel with dipole-dipole interaction of sodium carboxylates as the main driving force. The hydrogel showed properties in selective dye adsorption and sustainable release. Fig. 1 Chemical structures of GA (1) and sodium glycyrrhetinate (2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 55 publications
1
29
0
1
Order By: Relevance
“… 54 , 349 , 350 Lu et al recently reported that sodium glycyrrhetinate ( 84 ) is able to form a hydrogel with a CGC of 5.6 wt %, and the authors suggested the dipole–dipole interaction of sodium carboxylates as the main driving force for the hydrogelation of 84 . 351 Another related interesting work is the hydrolysis of succinated triamcinolone acetonide which forms triamcinolone acetonide and results in hydrogelation. 352 …”
Section: Molecular Designmentioning
confidence: 99%
“… 54 , 349 , 350 Lu et al recently reported that sodium glycyrrhetinate ( 84 ) is able to form a hydrogel with a CGC of 5.6 wt %, and the authors suggested the dipole–dipole interaction of sodium carboxylates as the main driving force for the hydrogelation of 84 . 351 Another related interesting work is the hydrolysis of succinated triamcinolone acetonide which forms triamcinolone acetonide and results in hydrogelation. 352 …”
Section: Molecular Designmentioning
confidence: 99%
“…Among these materials mentioned above, polymeric hydrogel is one of the most promising adsorbents due to their facile preparation, low-cost, and high-specic loading capacity. 12,13 Recently, various synthetic polymer based hydrogels have been fabricated, 14,15 such as poly(acrylic acid) (PAA) and polyacrylamide hydrogels, these obtained hydrogels demonstrated certain adsorption capability as effective adsorbent for various contaminants. However, the usage of these synthetic polymer engineered hydrogels also face several inherent shortages, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the formation of the above-mentioned glycyrrhetinic-acid-based supramolecular gel requires the use of organic solvents, which greatly limits the application of glycyrrhetinic acid in the biomedical field. To solve this problem, the Ju group reported the first glycyrrhetinic-acid-based supramolecular hydrogel in 2013 [74]. The authors found that an opaque and thermally reversible hydrogel could be formed by slightly heating and dissolving a certain amount of sodium glycyrhizinate in an alkaline aqueous solution with pH > 9 and then cooling.…”
Section: Glycyrrhetinic Acid Based Low-molecular-weight Supramolecular Gelsmentioning
confidence: 99%